EFFICINCY OF SERIN AND NOMOLT AND COMBINATION WITH OILS AGAINST Aonidiella orientalis (NEWST.) AND Phyllocnistis citrella (STAINTON). - AL- Jameel , Sahil K.; Jarjees, Salim J. (Diyala Agricultural Sciences Journal, 2013)
Field experiments were conducted on citrus trees infested by Aonidiella orientalis (Newst.) and Phyllocnistis citrella (STAINTON) in Mosul during 2007. Results indicated reduction in the rate of Aonidiella orientalis (Newst.) infestation. Treatments were in the following order: Serin + oil, Nomolt + oil , Serin and oil these treatments significantly decreased No. of nymph / leaflets to 0.90 ,1.10 ,1.45 and 2.50 nymph /leaf respectively after 14 days. The results indicated that treatments which combine by serin + oil give high efficiency against citrus leaf miner to reduce percentage and intensity of infestation. The treatments are descending order was as follows: Serin + oil ,Nomolt + oil, Serin and oil. Results were encouraging to introduces oils into Aonidiella orientalis (Newst.) and citrus leaf miner Phyllocnistis citrella (Stainton) control program either alone or in combination with insecticides.